A Role for P-Glycoprotein in Clearance of Alzheimer Amyloid β -Peptide from the Brain - Wang, Wei; M. Bodles-Brakhop, Angela; W. Barger, Steven (Current Alzheimer Research, 2016)
Most data indicates that Alzheimer’s disease involves an accumulation of amyloid β - peptide (Aβ) in the CNS and that sporadic cases arise from a deficiency in Aβ clearance. Considerable attention has been given to mechanisms by which Aβ might be transported between the brain and blood, and evidence suggests that p-glycoprotein, also known as the multi-drug resistance (MDR) protein (product of the ABCB1 gene), plays a role in Aβ transport across the blood-brain barrier (BBB). We tested this possibility through two approaches: First, wild-type and MDR1A-knockout mice were compared after intravenous injection of [125I]-labeled Aβ; after 60 min, homogenates of brain parenchyma were subjected to γ-counting of TCA-precipitable material, and histological sections of brain were subjected to autoradiography. Second, MDR1Aknockout mice were crossed with Tg2576 APP transgenic mice, a line that routinely accumulates Aβ in the brain; SDS and formic acid extracts of brain homogenates were assessed for Aβ levels by ELISA. Each of these approaches yielded data indicating that Aβ accumulates to a greater degree in mice lacking MDR1A. These findings confirm other reports linking p-glycoprotein to Aβ clearance across the BBB and have important implications for Alzheimer’s disease genetics, pharmacology, and epidemiology.
Keywords: blood-brain barrier